Why EMU is irrelevant for the German economy - Adam Posen (Goethe University Frankfurt, Center for Financial Studies (CFS), 1998)
No one seems to be neutral about the effects of EMU on the German economy. Roughly speaking, there are two camps: those who see the euro as the advent of a newly open, large, and efficient regime which will lead to improvements in European and in particular in German competitiveness; those who see the euro as a weakening of the German commitment to price stability. From a broader macroeconomic perspective, however, it is clear that EMU is unlikely to cause directly any meaningful change either for the better in Standort Deutschland or for the worse in the German price stability. There is ample evidence that changes in monetary regimes (so long as non leaving hyperinflation) induce little changes in real economic structures such as labor or financial markets. Regional asymmetries of the sorts in the EU do not tend to translate into monetary differences. Most importantly, there is no good reason to believe that the ECB will behave any differently than the Bundesbank.
urn:nbn:de:hebis:30-9496
Keywords: E5; F3; 330; EMU; central bank; monetary policy; Germany